Positioning in classroom discourse studies: a state-of-the-art review. Issue 2 (4th May 2018) - Kayi-Aydar, Hayriye; Miller, Elizabeth R.
Abstract: This article reviews the growing number of studies that have drawn on positioning theory in exploring the interactional dynamics of classroom discourse. It discusses key concepts of the theory, provides an overview of empirical studies that focus on student positioning, in 'mainstream' content classrooms and classrooms that include learners or speakers of additional languages, as well as studies that concentrate on teacher positioning. As we summarise and critically synthesise these studies, we discuss implications of positioning for learning and teaching, offer a critique of positioning theory and provide guidelines for future research in this area.